CORRELATION OF PLASMINOGEN ACTIVATOR INHIBITOR AND ANGIOTESIN-CONVERTING ENZYME GENES WITH MISSED MISCARRIAGE IN THE FIRST HALF OF PREGNANCY (CAHIERS MAGELLANES-NS, 2024)
Background: Recurrent miscarriage stands as a significant public health issue, affecting 2%-5% of women in their childbearing years. It is characterized by the occurrence of three or more consecutive pregnancy losses before reaching viability, encompassing all miscarriages from conception to the 20th week of gestation. Thrombotic disorders are identifiable in 40–50% . Our Aim is To study the relation of the common polymorphisms in Angiotensin converting enzyme and plasminogen activator inhibitor-1with recurrent miscarriage.Patients and Methods: This comparative observational prospective case-control study was carried out at Duhok Hospital for Obstetrics and Gynecology during the period from January 1st to September 1st, 2023, it included 100 married women in age range (18-42 years), as 50 women with a history of three or more miscarriages during the first half of pregnancy and fifty women as controls with a history of at least one successful pregnancy. Data were collected through a questionnaire form and blood tests targeting these thrombophilia genes (Angiotensin converting enzyme and plasminogen activator inhibitor-1).Results: This study showed that women with history of Recurrent miscarriage had a significant association with plasminogen activator inhibitor l with (P= 0.009), but no association with angiotensin-converting enzyme genes, the (P= 0.275). In addition, the recurrent miscarriage has a significant association with parity (P ≤ 0.001), while did not associated with each BMI and supplement taking.     Conclusions: The genetic marker PAI-1 is playing a discernible role in recurrent   miscarriage while ACE gene does not show any significant impact.